Population structure and genetic diversity of Fusarium species on solanaceous crops in the North-Western Himalayas - Tasmeen J. Parihar; Sehla Khursheed; Syed Shoaib Mubashir; Shafqat Mehraj; Zahoor A. Bhat; Asif B. Shikari; Niyaz A. Dar; M. Ashraf Bhat; Mehraj D. Shah; Khalid Z. Masoodi (Indian Phytopathology, 2026)

Implementing QbD for Nano-Pharmaceuticals and Complex Formulations to Achieve Predictable and High-Quality Outcomes - Rohan Panwar; Anuradha Mishra; Abhisar Sahu; Syed Naved Quadri; M. Z. Abdin; Saman Fatima (AAPS PharmSciTech, 2026)

Electron-rich sulfur sites and dual interfacial bonds in S-scheme heterojunction enable high quantum yield and stable hydrogen production - Sharafat Ali; Sajjad Ali; Shu-Long Li; Ahmed Ismail; Sher Ali; Pir Muhammad Ismail; Syed Ul Hasnain Bakhtiar; Fazal Raziq; Mohammad Z. Rahman; Liang Qiao (Chemical Engineering Journal, 2026)

Energy-efficient carbon capture from industrial point sources via commercially available green solvent and hollow fiber membrane contactors - Mary H. Irwin; Nicholas Gregorich; Zachary Coin; Ramesh Bhave; Ilia Ivanov; Robert Sacci; Gernot Rother; David S. Sholl; Syed Z. Islam (Chemical Engineering Journal, 2025)

Toxic Metals in the Workplace: Assessing Heavy Metal Contaminants in Indoor Dust of Auto Parts Stores and Their Impact on Health of Employees - Nadeem Ali; Sultan H. Alamri; Jahan Zeb; Mohammad Rehan; Nisreen Rajeh; Nabil Alhakamy; Mohamed I. Orif; Muhammad Imtiaz Rashid; Syed Ali Musstjab Akber Shah Eqani; Hani Z. Asfour (Water, Air, & Soil Pollution, 2025)

Unveiling the anti-diabetic effects of Garcinia hombroniana fruit pericarp and leaf : in vitro radical scavenging, alpha-glucosidase inhibition, pharmacokinetics, and in silico molecular docking of Q-TOF-LCMS identified compounds - Qamar Uddin Ahmed; Siti Nur Aina Atirah Ali; Nurul Nadira Shahira Abdul Jalil; ABM Helal Uddin; Mohd Salleh Rofiee; Syed Adnan Ali Shah; Mohd Zaki Salleh; Syed Atif Abbas; Mohammad Z. Ahmed; Md Zaidul Islam Sarker; Md. Abdur Rashid Mia (Natural Product Research, 2025)

Photocatalytic and photoelectrochemical H2 generation for sustainable future: Performance improvement, techno-economic analysis, and life cycle assessment for shaping the reality - Musfekur Rahman Dihan; Tanzim Ur Rahman; Md.Atquj Jaman Riad Khan; Tabassum Sunjida Banhi; Shoumik Sadaf; Md Sumon Reza; Shammya Afroze; Syed Z. Islam; Md.Shahinoor Islam (Fuel, 2025)

A remote sensing and GIS-based analysis of forest cover changes and carbon sequestration trends over three decades - Ali Raza; Neyha Rubab Syed; Romana Fahmeed; Siham Acharki; Sajjad Hussain; Muhammad Zubair; Dinesh Kumar Vishwakarma; Arpit Gaur; Bhaskar Pratap Singh; Abdelaziz M. Okasha; Ahmed Z. Dewidar; Mohamed A. Mattar (Environmental Development, 2025)

Secondary metabolite profile of Streptomyces spp. changes when grown with the sub-lethal concentration of silver nanoparticles: possible implication in novel compound discovery - Merajuddin Khan; Hamad Z. Alkhathlan; Syed Farooq Adil; Mohammed Rafi Shaik; Mohammed Rafiq H. Siddiqui; Mujeeb Khan; Shams Tabrez Khan (Antonie van Leeuwenhoek, 2024)

Correction: Cobalt Uptake by Food Plants and Accumulation in Municipal Solid Waste Materials Compost-amended Soil: Public Health Implications - Zafar Iqbal Khan; Asma Ashfaq; Kafeel Ahmad; Aima Iram Batool; Mehwish Aslam; Tasneem Ahmad; Naunain Mehmood; Ijaz Rasool Noorka; Abdel-Rhman Z. Gaafar; Mohamed S. Elshikh; Syed Sikandar Habib; Riaz Khan; et al. (Biological Trace Element Research, 2024)

Cobalt Uptake by Food Plants and Accumulation in Municipal Solid Waste Materials Compost-amended Soil: Public Health Implications - Zafar Iqbal Khan; Asma Ashfaq; Kafeel Ahmad; Aima Iram Batool; Mehwish Aslam; Tasneem Ahmad; Naunain Mehmood; Ijaz Rasool Noorka; Abdel-Rhman Z. Gaafar; Mohamed S. Elshikh; Syed Sikandar Habib; Riaz Khan; et al. (Biological Trace Element Research, 2024)

PM2.5 concentration forecasting: Development of integrated multivariate variational mode decomposition with kernel Ridge regression and weighted mean of vectors optimization - Hai Tao; Iman Ahmadianfar; Leonardo Goliatt; Syed Shabi Ul Hassan Kazmi; Mohamed A. Yassin; Atheer Y. Oudah; Raad Z. Homod; Hussein Togun; Zaher Mundher Yaseen (Atmospheric Pollution Research, 2024)

Heavy metals prediction in coastal marine sediments using hybridized machine learning models with metaheuristic optimization algorithm - Zaher Mundher Yaseen; Wan Hanna Melini Wan Mohtar; Raad Z. Homod; Omer A. Alawi; Sani I. Abba; Atheer Y. Oudah; Hussein Togun; Leonardo Goliatt; Syed Shabi Ul Hassan Kazmi; Hai Tao (Chemosphere, 2024)

Dairy farmers’ knowledge, awareness and practices regarding bovine lameness in Malaysian dairy farms - M. B. Sadiq; S. Z. Ramanoon; R. Mansor; S. S. Syed-Hussain; W. M. Shaik Mossadeq (Tropical Animal Health and Production, 2024)

Biochar-layered double hydroxide composites for the adsorption of tetracycline from water: synthesis, process modeling, and mechanism - Mukarram Zubair; Mohammad Saood Manzar; Amjad El-Qanni; Hajira Haroon; Hissah A. Alqahtani; Maryam Al-Ejji; Nuhu Dalhat Mu’azu; Jwaher M. AlGhamdi; Shamsuddeen A. Haladu; Dana Al-Hashim; Syed Z. Ahmed (Environmental Science and Pollution Research, 2023)

Enhancing Biotic Stress Tolerance in Soybean Affected by Rhizoctonia solani Root Rot Through an Integrated Approach of Biocontrol Agent and Fungicide - Kiran Paliwal; Anjana Jajoo; Rupal Singh Tomar; Anil Prakash; Asad Syed; Jeberlin Prabina Bright; R. Z. Sayyed (Current Microbiology, 2023)

Toxic dye removal, remediation, and mechanism with doped SnO2-based nanocomposite photocatalysts: A critical review - Hridoy Roy; Tanzim Ur Rahman; Md. Atquj Jaman Riad Khan; Md. Rashid Al-Mamun; Syed Z. Islam; Md. Abdul Khaleque; Md. Ikram Hossain; Md. Zaved Hossain Khan; Md. Shahinoor Islam; Hadi M. Marwani; Aminul Islam; Md. Munjur Hasan; et al. (Journal of Water Process Engineering, 2023)

Comparative transcriptomics unravels new genes imparting scab resistance in apple (Malus x domestica Borkh.) - Khalid Z. Masoodi; Nazeer Ahmed; Mudasir A. Mir; Basharat Bhat; Afshana Shafi; Sheikh Mansoor; Rovidha S. Rasool; Mifftha Yaseen; Zahoor A. Dar; Javid I. Mir; Syed Mudasir Andrabi; Nazir A. Ganai (Functional & Integrative Genomics, 2022)

Molecular communication network and its applications in crop sciences - Shakeel Ahmed; Jiandong Hu; Syed M. Z. A. Naqvi; Yanyan Zhang; Li Linze; Abdulraheem M. Iderawumi (Planta, 2022)

MYB-6 and LDOX-1 regulated accretion of anthocyanin response to cold stress in purple black carrot (Daucus carota L.) - Niyaz A. Dar; Mudasir A. Mir; Javid I. Mir; Sheikh Mansoor; Wasia Showkat; Tasmeen J. Parihar; Syed Anam Ul Haq; Shabir H. Wani; Gul Zaffar; Khalid Z. Masoodi (Molecular Biology Reports, 2022)

Explicating genetic diversity based on ITS characterization and determination of antioxidant potential in sea buckthorn (Hippophae spp.) - Syed Anam ul Haq; Mudasir A. Mir; Sameena M. Lone; Aqleema Banoo; Fauzia Shafi; Shakeel A. Mir; Javeed I. A. Bhat; Rizwan Rashid; Shabir H. Wani; T. H. Masoodi; M. N. Khan; Firdous A. Nehvi; et al. (Molecular Biology Reports, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

ACC deaminase and antioxidant enzymes producing halophilic Enterobacter sp. PR14 promotes the growth of rice and millets under salinity stress - A. Sagar; R. Z. Sayyed; P. W. Ramteke; S. Sharma; Najat Marraiki; Abdallah M. Elgorban; Asad Syed (Physiology and Molecular Biology of Plants, 2020)

Amyloid Beta 25–35 induces blood-brain barrier disruption in vitro - Elvis Cuevas; Hector Rosas-Hernandez; Susan M. Burks; Manuel A. Ramirez-Lee; Aida Guzman; Syed Z. Imam; Syed F. Ali; Sumit Sarkar (Metabolic Brain Disease, 2019)

Evaluation of climate-induced waterlogging hazards in the south-west coast of Bangladesh using Geoinformatics - Syed M. Tareq; M. Tauhid Ur Rahman; A. Z. M. Zahedul Islam; A. B. M. Baddruzzaman; M. Ashraf Ali (Environmental Monitoring and Assessment, 2018)

Characterization of Biaxial Stretch as an In Vitro Model of Traumatic Brain Injury to the Blood-Brain Barrier - Hector Rosas-Hernandez; Elvis Cuevas; Claudia Escudero-Lourdes; Susan M. Lantz; Nancy P. Gomez-Crisostomo; Nasya M. Sturdivant; Kartik Balachandran; Syed Z. Imam; William Slikker; Merle G. Paule; Syed F. Ali (Molecular Neurobiology, 2018)

Prevalence of lameness, claw lesions, and associated risk factors in dairy farms in Selangor, Malaysia - M. B. Sadiq; S. Z. Ramanoon; R. Mansor; S. S. Syed-Hussain; W. M. Shaik Mossadeq (Tropical Animal Health and Production, 2017)

Temporal dynamics of land use/land cover change and its prediction using CA-ANN model for southwestern coastal Bangladesh - M. Tauhid Ur Rahman; Faheemah Tabassum; Md. Rasheduzzaman; Humayra Saba; Lina Sarkar; Jannatul Ferdous; Syed Zia Uddin; A. Z. M. Zahedul Islam (Environmental Monitoring and Assessment, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Iron Oxide Nanoparticles Induce Dopaminergic Damage: In vitro Pathways and In Vivo Imaging Reveals Mechanism of Neuronal Damage - Syed Z. Imam; Susan M. Lantz-McPeak; Elvis Cuevas; Hector Rosas-Hernandez; Serguei Liachenko; Yongbin Zhang; Sumit Sarkar; Jaivijay Ramu; Bonnie L. Robinson; Yvonne Jones; Bobby Gough; Merle G. Paule; et al. (Molecular Neurobiology, 2015)

The molecular phylogenetic signature of Bali cattle revealed by maternal and paternal markers - S. M. F. Syed-Shabthar; M. K. A. Rosli; N. A. A. Mohd-Zin; S. M. N. Romaino; Z. A. Fazly-Ann; M. C. Mahani; O. Abas-Mazni; R. Zainuddin; S. Yaakop; B. M. Md-Zain (Molecular Biology Reports, 2013)

Emergence of amantadine-resistant avian influenza H5N1 virus in India - C. Tosh; H. V. Murugkar; S. Nagarajan; S. Tripathi; M. Katare; R. Jain; R. Khandia; Z. Syed; P. Behera; S. Patil; D. D. Kulkarni; S. C. Dubey (Virus Genes, 2011)

Effect of triploidization on juvenile African catfish (Clarias gariepinus) - A. Karami; A. Christianus; Z. Ishak; S. C. Courtenay; M. A. Syed; M. Noor Azlina; H. Noorshinah (Aquaculture International, 2010)

Hexavalent molybdenum reduction to Mo-blue by Acinetobacter calcoaceticus - M. Y. Shukor; M. F. Rahman; Z. Suhaili; N. A. Shamaan; M. A. Syed (Folia Microbiologica, 2010)

Olfactory and behavioural responses of tsetse flies, Glossina spp., to rumen metabolites - Vincent Harraca; Z. Syed; P. M. Guerin (Journal of Comparative Physiology A, 2009)

Bacterial reduction of hexavalent molybdenum to molybdenum blue - M. Y. Shukor; M. F. Rahman; Z. Suhaili; N. A. Shamaan; M. A. Syed (World Journal of Microbiology and Biotechnology, 2009)

Spatio-temporal variations in water quality of Nullah Aik-tributary of the river Chenab, Pakistan - Abdul Qadir; Riffat Naseem Malik; Syed Z. Husain (Environmental Monitoring and Assessment, 2008)

Atrial cell action potential parameter fitting using genetic algorithms - Z. Syed; E. Vigmond; S. Nattel; L. J. Leon (Medical & Biological Engineering & Computing, 2005)

Genetic mapping and QTL analysis of fiber-related traits in cotton (Gossypium) - M. Mei; N. H. Syed; W. Gao; P. M. Thaxton; C. W. Smith; D. M. Stelly; Z. J. Chen (Theoretical and Applied Genetics, 2004)

Lack of hydroxyl radical generation upon central administration of methamphetamine in rat caudate nucleus: A microdialysis study - Frederico C. Pereira; Tice R. Macedo; Syed Z. Imam; Carlos F. Ribeiro; Syed F. Ali (Neurotoxicity Research, 2004)

Antennal Responses of the Two Host Races of the Larch Bud Moth, Zeiraphera diniana, to Larch and Cembran Pine Volatiles - Z. Syed; P. M. Guerin; W. Baltensweiler (Journal of Chemical Ecology, 2003)

1-Octen-3-Ol Isolated from Bont Ticks Attracts Amblyomma variegatum - C. McMahon; P. M. Guerin; Z. Syed (Journal of Chemical Ecology, 2001)